Accountability of armed opposition groups in international law - Zegveld, Liesbeth (Cambridge University Press, 2002)
Armed opposition groups generally fight governments, seeking overthrow and/or secession. But who is accountable under international law for the acts committed by these groups, or for the failure to prevent these acts? Zegveld examines the need legally to identify the parties involved when armed internal conflict arises, and the reality of their demand for rights. Although currently most armed conflicts are internal, they remain largely uncharted territory in law. This award-winning study will be of interest to academics, postgraduate students and professionals involved with armed conflict and international relations.